(untitled) (Conferencea, 2023)
Social conflicts are an integral part of social life and arise due to different opinions, interests and values. The resolution of social conflicts is an important task for creating a harmonious and just society. In recent years, there have been changes in approaches to resolving these conflicts, taking into account the new challenges and requirements of the modern world. Some of these changes include the following: Dialogue and participation: Instead of the use of force or authoritarian methods of conflict resolution, dialogue between conflicting parties is becoming increasingly important. The emphasis is shifting to the participation of all stakeholders in the conflict resolution process. This helps to understand different points of view and seek agreement.